Monte Carlo simulations of backscattered light from an embedded object in a biological tissue - Yadhunath, Srushti (2016)
With advancement in light illumination and collection technologies as well as computation capabilities, the use of optics in biomedicine to study, diagnose and provide therapy is expanding. This project aims to study a forward problem in tissue optics where for the given set of optical properties in a theoretical tissue model of interest, diffuse reflectance measurements are studied. The theoretical tissue model simulated is the squamous cell carcinoma. A homogenous (single layer) and non-homogeneous (two layer) semi-infinite turbid media are being studied with a spherical target object embedded in them which could potentially represent a tumor. A set of parameters in the tissue including target depth, target radius and input laser beam radius have been varied and their effects on total diffuse reflectance and radial diffuse reflectance are studied. The Monte Carlo Multi-Layer-Embedded Object (MCML-EO) source code has been used to carry out the simulations. One variable is varied at a time to study its effect on the diffuse reflectance values and examine if there is an overall trend that can be derived. Results indicate that for both the single layer and double layer models, increase in target depth significantly reduces the diffuse reflectance signals and increase in target radius significantly increases diffuse reflectance measured. When these parameters are measured across a range of increasing laser beam radius values, the total diffuse reflectance measurements show an increase. A more broad analysis on the effects of laser beam radius needs to be conducted for more conclusive results.